Genotype and phenotype variability studies in fenugreek (Trigonella foenum-graecum L.) accessions in Kaffa Zone, South West Ethiopia - Menamo, A A Wojo, S Alamerew, A Nebiyu, T (Journal of Spices and Aromatic Crops, 2016)
The present investigation was conducted on 36 geographically diverse Ethiopian accessions of fenugreek with an objective to study the extent of genetic and phenotypic variation among yield and its related traits. The accessions differed significantly for most of the characters and exhibited a relatively wide range. These characters indicated existence of variation among the tested accessions. High GCV was only observed in number of secondary branches per plant. High PCV were observed in number of primary and secondary branches per plant, number of seeds per pod, and 1000-seeds weight. High heritability values were observed in the number of seed per pod (63.1%), plant height (65.3%), biological yield per plot (80.1%), seed yield per plot (89.0%), day to maturity (80.8%), and day to flowering (71.4%). High genetic advance was observed for days to maturity, number of pod per plant, number of secondary branches per plant, biological yield and seed yield per plot. Seed yield per plot had positive and significant genotypic correlations with all traits except days to 50% flowering and plant height. Seed yield per plot had positive and significant phenotypic association with number of primary branches and plant height at maturity. This study revealed that there is good scope of concurrent improvement in yield by exploiting the Ethiopian germplasm of fenugreek.